The elements of police hostage and crisis negotiations : critical incidents and how to respond to them - Greenstone, James L. (Hostage and crisis negotiation, 2005)
Run a safe and successful crisis negotiation?from start to finish! The Elements of Police Hostage and Crisis Negotiations: Critical Incidents and How to Respond to Them reduces the negotiation procedures for hostage, barricaded, and suicide incidents to their basic elements, providing quick and easy access to the information you need-from the initial call-out to the final debriefing. Based on field-tested principles proven to work, the book also includes newly developed and highly specialized techniques for more experienced negotiators. Author James L. Greenstone provides a user-friend.